Maximized Effective Transmission Rate Model for Advanced Neighbor Discovery Process in Bluetooth Low Energy 5.0 - Shan, Gaoyang; Roh, Byeong Hee (IEEE Internet of Things Journal, 2022)
Bluetooth low-energy (BLE) technology is one of the most promising communication technologies applicable to a variety of Internet of Things (IoT) services. The neighbor discovery process (NDP) plays a key role in BLE-enabled IoT services. The basic NDP (B-NDP) specified in BLE specification 4.0 has a limitation in supporting large numbers of BLE devices, owing to its use of three channels. To overcome the limitation of B-NDP, advanced NDP (A-NDP) has been recently introduced in BLE specification 5.0. However, most existing studies have focused on B-NDP, with very few studies having been conducted on A-NDP. In this article, we propose a model for analyzing the effective transmission rate for a BLE advertiser with an A-NDP operation. Using the proposed model, we also propose a performance model to maximize the transmission rate by optimally setting the BLE parameters. The proposed models are validated by comparing with extensive simulation results. It also demonstrates that the maximum transmission rate by the proposed models can be achieved with low energy consumption.
Keywords: Advanced neighbor discovery process; Bluetooth low energy; Bluetooth low energy specification 5.0; Device to device communication.; Device-to-Device communications; Effective transmission rate; Lower energies; Neighbor discovery; Performance Modeling; Advanced neighbor discovery process (A-NDP); BLE specification 50; bluetooth low energy (BLE); device to device communication; performance model